Does Project-Based Learning Equally Foster Critical and Creative Thinking? - Arfin Arfin; Melania Eva Wulanningtyas; Andy Leonardo Louismono; Oriza Stepanus (Riemann: Research of Mathematics and Mathematics Education, 2026)
This research explored the effectiveness of the Project-Based Learning (PjBL) instructional model in improving critical and creative thinking skills among students at SMAK 1 Bina Bakti Bandung, Indonesia. Employing a one-group pretest-posttest quasi-experimental design, the research examined how students’ critical and creative thinking skills developed after participating in a series of PjBL learning activities in polynomial topic. The findings revealed significant improvements in both critical and creative thinking skills. Critical thinking showed notably increases in all indicators (analysis, synthesis, problem solving, inference, evaluation) with the most substantial changes in synthesis and problem solving. Likewise, creative thinking also showed a remarkable improvement in all indicators (flexibility, originality, elaboration, reflection, and fluency) particularly in elaboration and fluency. The effect sizes of critical and creative thinking were measured at 0.804 and 0.949 respectively, indicating the strong impact of PjBL in improving both domains. While critical thinking exhibited comparatively elevated scores both prior to and following the intervention, the extent of enhancement was more pronounced in creative thinking. It was suggested by these results that while a relatively strong foundation in critical thinking had already been demonstrated by the students, their creative thinking skills were particularly effectively enhanced by the implementation of PjBL.